Biology : - Presson, Joelle (McGraw Hill, 2008)
Presson/Jenner: Biology: Dimensions of Life, 1e is a one-semester biology text with an engaging, conversational style which encourages basic understanding of biology, issues, and applications leading students to a greater awareness of how they interact with the world around them. The goal of this text is to help students understand how biology relates to their lives and why they should develop a desire to obtain knowledge about science and biological issues